2017
DOI: 10.1002/polb.24317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer network on electrically induced reflection band broadening of cholesteric liquid crystals

Abstract: The reflection band of polymer stabilized cholesteric liquid crystals with negative dielectric anisotropy can be broadened by DC electric fields, which was ascribed to the pitch gradient caused by the motion of the structural chirality, that is, the polymer network. They systematically varied the mixture components, such as the photo‐initiator concentration, the monomer functionality, and the chiral dopant, to explore their influences on the reflection band broadening behavior. They learned how to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Using this methodology, Kent Optronics developed a product named as e-TransFlector, such an electrically switchable transreflective LC device can be rapidly and reversibly switched between full-color reflection, half-reflection, and fully transparent states through applying a low electric field as shown in Figure 5d-f. Several other research groups have also put extensive efforts to develop the cholesteric films with switchable reflection bandwidth. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] For example, Schenning and co-workers reported electrically switchable broadband photonic reflection in infrared regions by developing polymer network-stabilized cholesteric thin films. [99,100] White and co-workers found that broadband photonic reflection could be dynamically switched in polymer stabilized cholesteric LCs with negative dielectric anisotropy under DC electric fields, Figure 3.…”
Section: Cholesteric Superstructures Exhibiting Pitch Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this methodology, Kent Optronics developed a product named as e-TransFlector, such an electrically switchable transreflective LC device can be rapidly and reversibly switched between full-color reflection, half-reflection, and fully transparent states through applying a low electric field as shown in Figure 5d-f. Several other research groups have also put extensive efforts to develop the cholesteric films with switchable reflection bandwidth. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] For example, Schenning and co-workers reported electrically switchable broadband photonic reflection in infrared regions by developing polymer network-stabilized cholesteric thin films. [99,100] White and co-workers found that broadband photonic reflection could be dynamically switched in polymer stabilized cholesteric LCs with negative dielectric anisotropy under DC electric fields, Figure 3.…”
Section: Cholesteric Superstructures Exhibiting Pitch Gradientmentioning
confidence: 99%
“…and the underlying principle is that the pitch gradient came from field-induced motion of the structural chirality, i.e., the polymer network. [101][102][103][104] Yang and co-workers developed electrically switchable cholesteric reflectors by doping chiral ionic liquid (CIL) into liquid crystalline host with negative dielectric anisotropy. [105] Upon an electric field application, the cations and the anions of CIL moved toward the cathode and the anode, respectively.…”
Section: Cholesteric Superstructures Exhibiting Pitch Gradientmentioning
confidence: 99%
“…The main advantage of this setting is that the initial conditions for pulses at the input edge of the uniform BG segment may be manipulated by means of the preceding chirped BG, which provides a possibility of preparing the right mix of forward and backward fields. As in Bragg superstructures, light propagation in chirped gratings can be described by the standard coupled-mode theory [53,[56][57][58][59]. For slowly varying envelopes of forward and backward waves, Ef and Eb, the coupled-mode equations are written as [14,56]:…”
Section: Optical Signal Processing In Chirped Bragg Structuresmentioning
confidence: 99%
“…Depending on the location where the full polymerization of the reactive monomer (RM) completes from a low molecular weight liquid crystal solvent, the formed structure can be generally classified as a bulk polymer network or a surface localized polymer. Most prior studies were focused on the polymer network that stabilized LC on a rubbed polyimide layer and have shown that some parameters such as solubility parameters of RM in LC [ 12 ], the RM concentration in LC [ 13 , 14 ], LC materials [ 15 , 16 ], reactive monomers [ 17 ], ultraviolet (UV) curing intensity [ 18 ], and the UV curing temperature [ 19 , 20 ] could affect the resulting morphology and subsequent electro-optical behaviors. I. Dierking et al reported that monomer solubility played a primary role in determining network morphology in the polymer stabilized liquid crystal (PSLC) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%